The Image of the Gunung Padang Site as A Cultural Heritage in the Perspective of Pre-Iconographical - Syahid, Syahid; Widya Wardani, Winny Gunarti; Wulandari, Wulandari (Universitas Indraprasta PGRI, 2021)
The Gunung Padang site is one of the cultural heritages in the Cianjur area of West Java. The existence of a terraced punden building from the Megalithic era holds a lot of historical value which is very useful for public knowledge. Visualization of the site through information media is needed so that its image as cultural heritage can be better known by the public. Qualitatively, this study uses a visual communication design approach by paying attention to design elements as the formalistic aspects of pre-Iconographical. This is an initial study that describes one's own practical experience by observing various aesthetic aspects of cultural heritage objects, ranging from a point, line, field, shape, color, texture, and design principles. By conducting this pre-iconographical perspective, it will be possible to determine the appropriate media design to form the image of the Gunung Padang site as a cultural heritage. The results of this study indicate that photo books, either in print or electronically, can be chosen as a medium of information because it has the potential to build the visual perception of the reader. Photo books can also be chosen as information media that can build the image of the Gunung Padang site by examining the design principles that influence it. This study is expected to be a scientific reference for visual communication design practitioners who want to produce visual images of cultural heritage objects.